Induction, contradiction, counterexample (HL)

Contents

Induction

The base case is

  • n=0n = 0 for nNn \in \mathbb{N},
  • n=1n = 1 for nZ+n \in \mathbb{Z}^+,
  • n=3n = 3 for nZ+,n3n \in \mathbb{Z}^+, n \geq 3

The steps:

  1. Show true for $n = $ base case.
  2. Assume true for n=kn = k.
  3. Show true for n=k+1n = k+1
  4. Pbase caseP_\text{base case} is true; PkP_k is true     Pk+1\implies P_{k+1} is true; PnP_n is true for nbase case.n \geq \text{base case}.

Steps 1 and 3 should be done using LHS to RHS proofs.

In step 3, try to involve the assumption from step 2 as early as possible.

If need to work backwards, be sure to cross out rough work. The final solution presented to examiners must be LHS to RHS proofs for steps 1 and 3.

Example: Using induction, prove that (1+x)n1+nx(1 + x)^n \geq 1 + nx for all nZ+{n \in \mathbb Z^+} and {xRx1}{\{x\in\mathbb R \mid x \geq -1\}}.


The base case is when n=1n = 1.

(1+x)(1)=1+x=1+(1)x\begin{align*} (1 + x)^{(1)} &= 1 + x \\ &= 1 + (1)x \end{align*}

Thus true for n=1n = 1.

Note that x1x \geq -1 implies 1+x01 + x \geq 0.

Assume true for n=kn = k, ie

(1+x)k(1+kx)(1 + x)^k \geq (1 + kx)

Note: “Assume true for n=kn = k” means “if we know the question statement is true for some kk”. IB explicitly does not give marks for “let n=k{n = k}” or “assume n=k{n = k}”, which means something else.

Then for n=k+1n = k + 1

(1+x)k+1(1+x)k(1+x)(definitely non-negative)(1+kx)(1+x)(may be negative)=1+x+kx+kx2=1+(k+1)x+kx2\begin{align*} (1 + x)^{k + 1} &\geq (1 + x)^k (1 + x) \quad(\text{definitely non-negative})\\ &\geq (1 + kx)(1 + x) \quad(\text{may be negative})\\ &= 1 + x + kx + kx^2 \\ &= 1 + (k + 1)x + kx^2 \end{align*}

Since kx20kx^2\geq 0, this shows that

(1+x)k+11+(k+1)x(1 + x)^{k + 1} \geq 1 + (k + 1)x

PkP_k is true     Pk+1\implies P_{k+1} is true; P1P_1 is true means PnP_n is true for n1n \geq 1 \qed

A stronger version of the above example is by breaking into even nn and odd nn, then using two base cases of n=0n = 0 and n=1n = 1, and showing Pk    Pk+2P_k \implies P_{k+2} means that (1+x)n1+nx{(1+x)^n \geq 1 + nx} for nN{n \in \mathbb N} and {xRx2}{\{x\in\mathbb R \mid x \geq -2\}} (other than the case n=0,x=1n = 0, x = -1 which is 000^0 or indeterminate.)

Example: (From The Art and Craft of Problem Solving) Prove using induction that 7n1{7^n - 1} is divisible by 66 for all nZ+n\in\mathbb Z^+.


For n=1n = 1, 7117^1 - 1 is 66, which is a multiple of 66.

Assume true for n=kn = k, or 7k1=6p{7^k - 1 = 6p}, for some pZ+{p \in \mathbb Z^+}.

Then for n=k+1n = k + 1

7k+11=77k1=77k7+6=7(7k1)+6=76p+6=6(7p+1)\begin{align*} 7^{k + 1} - 1 &= 7\cdot 7^k - 1 \\ &= 7\cdot 7^k - 7 + 6 \\ &= 7\cdot (7^k - 1) + 6 \\ &= 7\cdot 6p + 6 \\ &= 6 (7p + 1) \end{align*}

PkP_k is true     Pk+1\implies P_{k+1} is true; P1P_1 is true means PnP_n is true for n1n \geq 1 \qed

As an extension (beyond HL), there is also strong induction, in which we assume true for nkbase case,n,kZ{ n \geq k \geq \text{base case},\, n,k \in \mathbb Z}.

Contradiction

Contradiction works by assuming the complement (opposite) of what you are trying to show, reaching a false conclusion, which invalidates the assumption.

There are two cases.

single proposition

The first case is “show [some statement] is true”, with the first step to “assume [some statement] is false”.

  • “There exists … ” becomes “Assume there is no …”, vice versa.
  • “This is an infinite number of …” becomes “Assume there is a list of all …”
  • 63\sqrt[3]6 is irrational” becomes “Assume 63=pq,p,qZ+\sqrt[3]6 = \frac{p}{q}, \,p, q \in \mathbb Z^+ and pp and qq have no common factors.”
  • f(x)>yf(x) > y becomes “Assume f(x)yf(x) \leq y.”

Example: (Adapted from video by blackpenredpen ) Prove by contradiction that a2+b2=4c+3a^2 + b^2 = 4c + 3 has no integer solutions.


Assume there is a solution. Since right side is odd (EVEN + ODD = ODD), it follows that a2+b2a^2 + b^2 is odd, and that one of aa and bb is even, and other one is odd.

In the case aa is even and bb is odd, and (2m,2n+1,c)(2m, 2n + 1, c) is a solution for (a,b,c)(a, b, c). It follows that

(2m)2+(2n+1)2=4m2+4n2+4n+1=4(m2+n2+n)+14c+3=4(m2+n2+n)+12=4(m2+n2+nc)\begin{align*} (2m)^2 + (2n + 1)^2 &= 4m^2 + 4n^2 + 4n + 1 \\ &= 4(m^2 + n^2 + n) + 1 \\ 4c + 3 &= 4(m^2 + n^2 + n) + 1 \\ 2 &= 4(m^2 + n^2 + n - c) \end{align*}

This is a contradiction because left side is not a multiple of 44 but right side is. (More explicitly, when dividing both sides by 2, we have ODD on the left side and EVEN on the right). Hence (2m,2n+1,c)(2m, 2n + 1, c) is not a solution.

Since b2+a2=4c+3b^2 + a^2 = 4c + 3 has the same solutions as a2+b2=4c+3a^2 + b^2 = 4c + 3, (2n+1,2m,c)(2n + 1, 2m, c) is also not a solution. Both cases have no solution \qed

Example: Prove by contradiction that 63\sqrt[3]6 is irrational.


Assume 63=pq,p,q,Z+\sqrt[3]6 = \frac pq, \,p, q, \in \mathbb Z^+ and p,qp, q are coprime, ie have no common factors.

6=p3q36q3=p3\begin{align*} 6 &= \frac{p^3}{q^3}\\ 6q^3 &= p^3 \end{align*}

Since 6q36q^3 is even, then p3p^3 and pp are even, so p=2k,kZ+p = 2k, \, k\in\mathbb Z^+.

6q3=(2k)36q3=8k33q3=4k3\begin{align*} 6q^3 &= (2k)^3 \\ 6q^3 &= 8k^3 \\ 3q^3 &= 4k^3 \end{align*}

Since 4k34k^3 is even, then q3q^3 and qq are even.

This contradicts the assumption that pp and qq are coprime. In other words, the contradiction is there is a more simplified fraction than the simplest fraction. Hence 63\sqrt[3]6 is irrational \qed

if A then B

The second case is “if AA then BB”, with the first step to “assume AA AND not BB”. It is at times interchangeable with the first, but this helps with longer propositions or statements.

Example: Prove by contradiction that if a2+b2=c2a^2 + b^2 = c^2 and a,b,cZa, b, c\in \mathbb Z, then at least one of aa and bb is even.


Assume a2+b2=c2,a,b,cZa^2 + b^2 = c^2,\, a, b, c \in\mathbb Z and aa and bb are both odd. This means for p,qZ{p, q \in \mathbb Z}, let a=2p+1{a = 2p + 1}, b=2q+1{b = 2q + 1}.

(2p+1)2+(2q+1)2=4p2+4p+1+4q2+4q+1=c24(p2+p+q2+q)+2=c2\begin{align*} (2p+1)^2 + (2q+1)^2 = 4p^2 + 4p + 1 + 4q^2 + 4q + 1 &= c^2 \\ 4(p^2 + p + q^2 + q) + 2 = c^2 \end{align*}

cc is even. Let c=2r,rZc = 2r,\,r\in\mathbb Z

4(p2+p+q2+q)+2=(2r)2=4r2\begin{align*} 4(p^2 + p + q^2 + q) + 2 &= (2r)^2 \\ &= 4r^2 \end{align*}

This is a contradiction as left side is not a multiple of 44 (remainder 22), but right side is.

Hence by contradiction the statement requires aa and/or bb to be even \qed

Example: Prove using contradiction that sinxcosx1\sin x - \cos x \geq 1 for all x[π2,π]{x\in\left[\frac\pi2, \pi\right]}.


In quadrant II, sinx0\sin x \geq 0 and cosx0\cos x \leq 0, and they cannot be zero at the same time. So we can immediately show that sinxcosx>0{\sin x - \cos x > 0}, and sinxcosx0{\sin x \cos x \leq 0}.

Assume that sinxcosx<1\sin x - \cos x < 1 for some x[π2,π]{x\in\left[\frac\pi2, \pi\right]}.

Then

(sinxcosx)2=sin2x2sinxcosx+cos2x=12sinxcosx\begin{align*} (\sin x - \cos x)^2 &= \sin^2 x -2\sin x\cos x + \cos^2 x \\ &= 1 - 2 \sin x \cos x \end{align*}

Since we squared 0<sinxcosx<10 < \sin x - \cos x < 1, we see that

12sinxcosx<12sinxcosx<0sinxcosx>0after division by 2\begin{align*} 1 - 2\sin x \cos x &< 1 \\ - 2 \sin x \cos x &< 0 \\ \sin x\cos x &> 0 \quad{\text{after division by }-2} \end{align*}

This contradicts sinxcosx0{\sin x \cos x \leq 0}.

Therefore, the assumption is wrong, and sinxcosx1{\sin x - \cos x \geq 1} for all x[π2,π]{x\in\left[\frac\pi2, \pi\right]}\qed

Note: It is insufficient to show that sinxcosx1\sin x - \cos x \geq 1 results in no inconsistencies, rather we needed to show sinxcosx<1\sin x - \cos x < 1 led to an inconsistency.

tips

In your working, you can use the following without proof:

  1. parities (odd vs even) when adding or multiplying two integers
  • odd ++ odd is even, even ++ even is even, odd ++ even is odd
  • odd ×\times odd is odd, even ×\times (odd or even) is even
  • even numbers are 2k2k; odd numbers are 2k+12k+1
  1. algebra rules, for both equations and inequalities

Common contradictions look like

  1. An equation is odd on one side but even on the other.
  2. (Extension:) A equation has a multiple of nn on one side but not on the other.
  3. A statement that is algebraically false.
  4. Existence of a smaller number than the smallest. (Existence of a large number than the largest.)

Disprove by counterexample

Provide a specific case and explain that it shows the statement is not always true.

Example: Kim claims that if an integer in base-1010

  • is greater than 11, AND
  • each digit is 1,3,7,1, 3, 7, or 99, AND
  • the digits are all different, AND
  • the digits do not sum to a multiple of 33

then the integer is prime.

Provide a counterexample and explain why Kim is incorrect.


9191 is greater than one; its digits are 99 and 11; 9+1=109 + 1 = 10 which is not a multiple of 33, but it is not prime as 91=7×13{91 = 7 \times 13 \qed}


11 is not a counterexample, because it is not greater than 11.

2323 is not a counterexample, because the statement does not apply to integers with a digit 22. The statement does not say what happens if an integer is prime.

3737 is not a counterexample, but rather an example for which the statement holds true.